Dance and Disruptive Bodies: Injuries and Lessons for Another Possible Theology - Méndez Montoya, Angel F. ca. 21. Jh. (Concilium, 2024)
In the documentary and video dance La Travesía: rodilla, pantorrilla, hombro, cadera (The Journey: Knee, Calf, Shoulder, Hip, Alejandro Atocha 2023), Tatiana Zugazagoitia, a Mexican choreographer and dancer, shares her deep life experience as a dancer who resists the western expectations of extremely slender and "able" bodies. Tatiana shares her life history ridden with severe physical injuries and major surgeries. Her body disrupts the conventions of Eurocentric dance canons. However, at the same time, it is a body that resignifies the dancing essence and agency of contemporary dance seen through the lens of "other," "twisted" contexts, that could be perceived as queer. This paper is an invitation to follow the pacing of the core elements of this audio-visual narrative in order to incorporate the epistemologies of dancing bodies suffering injuries and "disabilities" into theological forms of knowledge, thus expanding our notions regarding what is considered "dance," serving us to retrieve possible anthropological and theological lessons from vulnerable bodies. It is also an invitation to construct a critical discernment about everyday life choreographies amidst bodies whose disruption offers sapiential lessons to imagine another possible theology in the heart of our perichoretic relationship with God, the dancer par excellence.